Computation of the Binding Energies between Human ACE2 and Spike RBDs of the Original Strain, Delta and Omicron Variants of the SARS‐CoV‐2: A DFT Simulation Approach. Issue 12 (13th September 2022) - Yamacli, Serhan; Avci, Mutlu
Abstract: The receptor binding domain (RBD) of SARS‐CoV‐2 binds to human ACE2 leading to infection. In this study, the complexes that are formed by the attachment of the SARS‐CoV‐2 spike RBDs of the original strain, delta and omicron variants to the human ACE2 are investigated via density functional theory (DFT) simulations to obtain binding energies. The DFT computations are performed without fragmenting the interfaces to involve longer‐range interactions for improved accuracy, which is one of the primary features of the approach used in this study. Basis set superposition error corrections and van der Waals dispersions are also included in the DFT simulations. The binding energies of the SARS‐CoV‐2 spike RBDs of the original strain, delta and omicron variants to the human ACE2 are computed as −4.76, −6.68, and −11.77 eV, respectively. These binding energy values indicate that the binding of the omicron variant to the ACE2 is much more favorable than the binding of the original strain and the delta variant, which constitute a molecular reason for the takeover of the omicron variant. The binding energies and the decomposition of these energies found in this study are expected to aid in the development of neutralizing agents. Abstract : The binding energies of the spike receptor binding domain of the original strain, delta and omicron variants to the human angiotensin‐converting enzyme 2 (ACE2) are obtained using density functional theory simulations. The binding energies of the original strain, delta and omicron variants to the human ACE2 are obtained as −4.76, −6.68, and −11.77 eV, respectively.